Sertifikat Halal Bagi Produk Makanan dan Minuman untuk Meningkatkan Citra UMKM di Kabupaten Blitar - Miranti Puspaningtyas; Sulastri Sulastri; Dhika Maha Putri (LPPM UNINUS, 2020)
Indonesia is a country with a most Muslim population, so that it will greatly affect the goods and services created by SMEs. This community service activity aims to give education for SME owners about the halal certificates importance, especially for food and beverage products in building consumer confidence and increasing sales. The problem that occurs at MSMEs today is the lack of attention to legality of halal to convince buyers that their products are quality guaranteed. The method used in community service activities is in the form of conseling and help to 33 SMEs. The number of samples chosen based on MSMEs that do not yet have a halal certificate. Based on the results of the conseling activities, all participants listened to presenters from the Blitar district MUI well and conveyed the complaints and concerns they faced to immediately register their products to have a halal certificate. After the question and answer session with the speakers, participants who were very enthusiastic then filled out the registration form for halal certificates. It can concluded that the extension activities have a 100% success rate, besides that the mentoring activities continue to run until now. The help will continue until the participants who send the halal certificate registration form get it. Based on the results of the above explanation, it can conclude that the SMEs really need the motivations and explanation of the correct flow in handling halal certificates. Very good enthusiasm will succeed if it is balance with real implementation of course in terms of halal certificate registration.